2021
DOI: 10.1007/s00441-020-03372-w
|View full text |Cite
|
Sign up to set email alerts
|

Odor hedonics coding in the vertebrate olfactory bulb

Abstract: Whether an odorant is perceived as pleasant or unpleasant (hedonic value) governs a range of crucial behaviors: foraging, escaping danger, and social interaction. Despite its importance in olfactory perception, little is known regarding how odor hedonics is represented and encoded in the brain. Here, we review recent findings describing how odorant hedonic value is represented in the first olfaction processing center, the olfactory bulb. We discuss how olfactory bulb circuits might contribute to the coding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…In addition, it has been shown that the perceptual dimensions of odor coding (i.e., the distribution of activity elicited by activated receptor neurons across the volume of the olfactory bulb) are related in humans and rats and that perceptual qualities can be represented as continuous spatial codes of the olfactory bulb glomeruli population (Auffarth et al, 2011). These hedonic representations in the olfactory bulb also appear to be centrally integrated, particularly within the reward system, in both mice and humans (Kermen et al, 2021; Midroit et al, 2021) or the olfactory tubercle in mice (Gadziola et al, 2015). Clearly, many areas beyond the olfactory bulb are involved in the hedonic processing of odors.…”
Section: Odor Hedonic Perception and Brain Processingmentioning
confidence: 99%
“…In addition, it has been shown that the perceptual dimensions of odor coding (i.e., the distribution of activity elicited by activated receptor neurons across the volume of the olfactory bulb) are related in humans and rats and that perceptual qualities can be represented as continuous spatial codes of the olfactory bulb glomeruli population (Auffarth et al, 2011). These hedonic representations in the olfactory bulb also appear to be centrally integrated, particularly within the reward system, in both mice and humans (Kermen et al, 2021; Midroit et al, 2021) or the olfactory tubercle in mice (Gadziola et al, 2015). Clearly, many areas beyond the olfactory bulb are involved in the hedonic processing of odors.…”
Section: Odor Hedonic Perception and Brain Processingmentioning
confidence: 99%
“…A key feature of our perceptual systems is to assign hedonic value, or valence, to stimuli to aid our decision to either approach or avoid them (Darwin, 2011;Lavender & Hommel, 2007;Öhman, 2007). In line with this, it has been hypothesized that the coding of valence is a dominant feature of the human olfactory system (Khan et al, 2007) and several areas of the olfactory system in animal models produce valencedependent responses (Blazing & Franks, 2020;Joussain et al, 2011;Kermen et al, 2021;Secundo et al, 2014). Likewise, in humans, both the olfactory bulb (OB) (Iravani et al, 2021a) and piriform cortex (PC) (Kato et al 2022) process representations of odor valence with inputs from the extended olfactory cortex (Rolls et al, 2003).…”
mentioning
confidence: 99%
“…Thereby, these authors mainly focus on how mammals extract spatial information from the environment. Recent findings describing how the hedonic value of an odorant, i.e., whether an odorant is perceived as pleasant or unpleasant, is represented in the OB circuitry are reviewed by Kermen et al (2021). The next review deals with the role of granule cells, the most prominent interneurons of the OB.…”
mentioning
confidence: 99%